Uma proposta de formação em serviço: professores na função de coordenadores pedagógicos na rede pública - Tardeli, Élida Aparecida (2014)
This study presents the results of research undertaken on the training of basic education teachers I designated to exercise the function coordinators at the State of São Paulo Public Network service. Constituted the research proposition shares of continuing education for the financial coordination such actions have been developed in eight guidelines developed in the formative encounters with a group of 24 newly appointed teachers. As the horizon of these meetings was : ( 1 ) creating a space that offers grants and opportunities for reflection on practice , ( 2 ) interaction between engineers, ( 3 ) design possible significant interventions in primary education schools , ( 4 ) reflecting starting this context training on probability of moving from a culture of individual work for the collective and cooperative work . The relevance of this research is to point out the strengths and needs of these beginning teachers on the job coordinator. It is postulated that the work allows building devices for a new design of training consistent with the needs of the professional pedagogical coordinator.